La difficile conquête du droit à l’information - Jean-Claude Sergeant (Revue Française de Civilisation Britannique)
Reforming the Official Secrets Act was also on the agenda of those who had been campaigning for Parliament to recognize the right to access official information. Their efforts had been thwarted by the natural inertia of successive governments who, however, invariably declared during each general election campaign that Freedom of Information was the cornerstone of democracy. The disappointment which met the FOI Bill presented by the Blair Government in 1999 reflected the frustration of those who had pinned their hopes on the White Paper published two years earlier. In its amended version, following concessions by the Cabinet, the new FOI Act marks, on the whole, a significant improvement on the previous situation. However, its delayed enforcement is a major cause for concern.